2018
DOI: 10.1007/s00431-018-3124-z
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration, body composition, dietary profile and eating behaviours among children and adolescents: a comparison between Portuguese acrobatic gymnasts

Abstract: Acrobatic gymnasts revealed low BF, short sleep duration and macro- and micronutrients inadequate intakes. The Female Athlete Triad was demonstrated by female adolescent gymnasts. What is Known: • Adequate dietary intake is an important resource for athletes' short and long-term health and performance. • There are no published studies in acrobatic gymnasts' sleep, body composition or dietary intake. What is New: • This study provides the first data on significant differences in energy intake and availability b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 35 publications
3
26
1
3
Order By: Relevance
“…All of these results are consistent with the body compositions reflected in other studies [60,62,63] and correlate with the evaluated somatotypes [63]. In this regard, similar results to those obtained in the present study regarding BMI, fat percentage, and fat-free mass have been shown previously [9,36,37]. The low fat mass percentage commonly observed in gymnasts has not been associated with health issues [63].…”
Section: Discussionsupporting
confidence: 93%
“…All of these results are consistent with the body compositions reflected in other studies [60,62,63] and correlate with the evaluated somatotypes [63]. In this regard, similar results to those obtained in the present study regarding BMI, fat percentage, and fat-free mass have been shown previously [9,36,37]. The low fat mass percentage commonly observed in gymnasts has not been associated with health issues [63].…”
Section: Discussionsupporting
confidence: 93%
“…Recent studies have investigated the prevalence of low EA in various sports [8,[13][14][15][16][17][18][19][20][21][22]. Prevalence ranges from 22% to 58% (Table 1).…”
Section: Low Energy Availabilitymentioning
confidence: 99%
“…Todas las ingestas diarias de energía y macronutrientes fueron significativamente diferentes según el sexo, a excepción de la fibra y energía en las mujeres y la proteína en los hombres (24) .…”
Section: Resultados Encontradosunclassified
“…Los test utilizados fueron variados, siendo los de mayor uso, el registro dietético de alimentos de 7 días (33,33%) (6,10,17,18,22) , el cuestionario de test de calidad de vida mediterránea o índice KIDMED (20%) (11,13,23) y el Registro de 3 días (20%) (12,16,24). En menor medida, se utilizaron el recordatorio 24 horas (14,19), así como, el FFQ (10,21) .…”
Section: Metodologíaunclassified
See 1 more Smart Citation